Echocardiographic agreement in the diagnostic evaluation for infective endocarditis - Lauridsen, Trine Kiilerich; Selton-Suty, Christine; Tong, Steven; Afonso, Luis; Cecchi, Enrico; Park, Lawrence; Yow, Eric; Barnhart, Huiman X.; Paré, Carlos; Samad, Zainab; Levine, Donald; Peterson, Gail; et al. (International Journal of Cardiovascular Imaging, 2016)
Echocardiography is essential for the diagnosis and management of infective endocarditis (IE). However, the reproducibility for the echocardiographic assessment of variables relevant to IE is unknown. Objectives of this study were: (1) To define the reproducibility for IE echocardiographic variables and (2) to describe a methodology for assessing quality in an observational cohort containing site-interpreted data. IE reproducibility was assessed on a subset of echocardiograms from subjects enrolled in the International Collaboration on Endocarditis registry. Specific echocardiographic case report forms were used. Intra-observer agreement was assessed from six site readers on ten randomly selected echocardiograms. Inter-observer agreement between sites and an echocardiography core laboratory was assessed on a separate random sample of 110 echocardiograms. Agreement was determined using intraclass correlation (ICC), coverage probability (CP), and limits of agreement for continuous variables and kappa statistics (κ weighted ) and CP for categorical variables. Intra-observer agreement for LVEF was excellent [ICC = 0.93 ± 0.1 and all pairwise differences for LVEF (CP) were within 10 %]. For IE categorical echocardiographic variables, intra-observer agreement was best for aortic abscess (κ weighted = 1.0, CP = 1.0 for all readers). Highest inter-observer agreement for IE categorical echocardiographic variables was obtained for vegetation location (κ weighted = 0.95; 95 % CI 0.92–0.99) and lowest agreement was found for vegetation mobility (κ weighted = 0.69; 95 % CI 0.62–0.86). Moderate to excellent intra- and inter-observer agreement is observed for echocardiographic variables in the diagnostic assessment of IE. A pragmatic approach for determining echocardiographic data reproducibility in a large, multicentre, site interpreted observational cohort is feasible.